ETYCZNE ASPEKTY FINANSOWANIA POTRZEB SOCJALNYCH ZE ŚRODKÓW PUBLICZNYCH - Łączkowski, Wojciech (Wydział Prawa i Administracji UAM, 2004)
Financing social needs with public resources should be compliant with the constitutional rule of social justice. However, the notion of justice is not defined as a legal term. Constitution of the Republic of Poland (chapter II, subchapter “Economic, social and cultural freedoms and rights”) seems to derive the notion of justice from egalitarianism. However, it leaves out the rule of subsidiarity and solidarity which are also mentioned in the Constitution. These rules in the context of financing social needs with taxpayers’ money do not allow clear-cut egalitarianism as it is unjust in this respect. On the other hand, the rule of subsidiarity and solidarity provides for a different division of tasks between different social structures and citizens and the assistance coming from the public resources should be granted to those who genuinely need it. It would allow for the implementation of the rule of justice to a much greater extent than mechanically understood equality does. Furthermore, it would help to avoid serious problems linked to the growing deficit of public spending and the need to keep a high rate of taxes and other duties and to alleviate numerous tensions and social conflicts. This does not mean, however, that the Government should abandon implementation of tasks related to social assistance but goes on to say that it should provide the conditions for organization and financing these tasks in a different way. It would require a decisive shift away from egalitarian concepts and the change of the law, to include the Constitution itself. Present solutions reveal inconsistency and internal incoherence of the Constitution.
ETHICAL ASPECTS OF FINANCING SOCIAL NEEDS WITH PUBLIC MONEY